Propriedades biológicas da proteína miosina-1 e do receptor dectina-1 na infecção in vitro por Trypanosoma cruzi - Costa, Mylla Spirandelli da (2020)
Trypanosoma cruzi (T. cruzi) is the etiologic agent of Chagas disease, belonging to Kinetoplastida group. It has three main evolutionary forms: trypomastigotes (infectious forms), amastigotes and epimastigotes (replicative forms in definitive host and vector insect, respectively). Myosins are motor proteins present in mammal cells and also in T. cruzi. In cells, they have several functions: phagocytosis, cytokinesis, signal transduction and organelles and particles traffic, and skeletal muscle is directly related to muscle contraction. In kinetoplastids, it participates in intraparasitic vesicle trafficking and flagellar assembly processes. Pentachloropseudilin (PCLP) is an inhibitor of type 1 myosin, belonging to both cells and the parasite. T. cruzi uses receptors, such as CXCR4 and bradykinin to obtain success in its invasion mechanisms. Dectin-1 is a lectin receptor and has been shown to be important in relevant diseases such as mycoses, colitis, obesity, alcoholic hepatitis, allergies and oncogenes. In addition to their ability to bind β-glucans, they also bind to troponin, Mycobacterium, Leishmania, galectin and galactosylated immunoglobulins. The aim of this work was investigate the role of T. cruzi and murine myoblasts (C2C12) myosin-1 and Dectin-1 receptor in macrophages during invasion process by T. cruzi. In the first chapter, we evaluated motility, ability to adhere to C2C12, ability to intracellular amastigotes multiply, ability to release secreted proteins, and capacity for T. cruzi after blocking with PCLP of cellular invasion. To assess cellular myosin, in addition to blocking and assessing the processes of cellular invasion by T. cruzi, intracellular lysosome traffic and CHMP4B role, involved in the formation of multivesicular bodies (MVBs), were evaluated. We initially observe that PCLP was not toxic to either T. cruzi or C2C12, but parasite myosin-1 inhibition altered its motility and the distance traveled by it, its ability to adhere to host cell, as well as its ability to invade them. By making rP21 available for T. cruzi with myosin-1 blocked at the time of invasion, this process is resumed, suggesting the possibility that this protein is not being secreted as it should. In addition, parasite intracellular multiplication capacity is compromised after 72 hours. When C2C12 myosin-1 is inhibited, invasion process by T. cruzi is also compromised due to impaired intracellular traffic, mainly of lysosomes. CHMP4B also interferes with parasite invasion process and is potentiated when we block myosin-1 from cells overexpressing this molecule. Therefore, myosin-1 from both parasite and cell has a fundamental role in infection progression by T. cruzi. In the second chapter, we performed invasion, multiplication assay and investigated rP21 relationship with Dectin-1. We observe that this receptor is important for T. cruzi infection success, because in its absence invasion and multiplication processes are outdated, in addition we saw that when make rP21 avaiable for parasites during invasion process, the index is resumed to WT cells level, upon further investigation, we observe that this was possible due to high expression of CXCR4 in knockout cells, suggesting a compensatory mechanism in absence of Dectin-1. Complementary studies are still needed to understand cellular mechanisms, but in general we can conclude that Dectin-1 is directly participating in cell invasion and multiplication process by T. cruzi.